Carotid plaque inflammation assessed with 18F‐FDG PET/CT is higher in symptomatic compared with asymptomatic patients. Issue 5 (15th January 2015) - Skagen, Karolina; Johnsrud, Kjersti; Evensen, Kristin; Scott, Helge; Krohg‐Sørensen, Kirsten; Reier‐Nilsen, Frode; Revheim, Mona‐Elisabeth; Fjeld, Jan Gunnar; Skjelland, Mona; Russell, David
<x xml:space="preserve">Abstract</x> Background Carotid artery plaque inflammation is thought to be an important marker of plaque vulnerability and increased stroke risk. Aim The main aim of this study was to assess the level of agreement between 2‐deoxy‐2‐[18F] fluoro‐D‐glucose (18F‐FDG) uptake on PET (positron emission tomography) scan in carotid plaques, with cerebrovascular symptoms, carotid plaque ultrasound echogenicity and histological assessments of plaque inflammation. Methods Thirty‐six patients with ≥70% carotid stenosis scheduled for carotid endarterectomy underwent a Colour Duplex ultrasound, 18F‐FDG PET/CT and blood tests less than 24 h prior to surgery. Plaques were defined as symptomatic when associated with ipsilateral cerebral ischemic symptoms within 30 days prior to inclusion. Plaques were assessed histologically following endarterectomy. The level of agreement between 18F‐FDG uptake (mean SUVmax and SUVmax), and target‐to‐background ratio, symptoms, plaque echolucency, and histological evidence of inflammation was assessed. Results The amount of 18F‐FDG uptake in plaques and the amount of inflammation on histological assessment were significantly correlated (r = 0·521, P = 0·003). 18F‐FDG uptake was significantly higher in symptomatic plaques with median SUVmax 1·75 (1·26–2·04) in symptomatic, and 1·43 (1·15–2·28) in asymptomatic patients (P = 0·03). 18F‐FDG uptake was also positively correlated with echolucency on Doppler ultrasound (P = 0·03). Conclusion 18F‐FDG uptake on PET/CT correlated with histological assessments of inflammation and was higher in patients with symptomatic compared with asymptomatic carotid artery plaques. These results support the use of 18F‐FDG PET/CT in the detection inflammation in carotid atherosclerosis, which may be of help in the detection of vulnerable plaques.